2015
DOI: 10.1089/apc.2014.0165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIV Virologic Failure Rates Between Patients with Variable Adherence to Three Antiretroviral Regimen Types

Abstract: Medication adherence is a major determinant of antiretroviral (ARV) treatment success and a significant challenge for HIV-positive patients, yet a well-defined adherence threshold to maintain virologic suppression on current ARV regimens remains unclear. The present study evaluated 1915 Kaiser Permanente Southern California HIV-positive patients on one of three regimen types: (1) emtricitabine-tenofovir-efavirenz (FTC-TDF-EFV); (2) emtricitabine-tenofovir (FTC-TDF) and raltegravir (RAL); and (3) FTC-TDF and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 18 publications
(24 reference statements)
2
56
1
Order By: Relevance
“…An 80-90% medication progression ratio to each of the three regimens was found to be associated with a virologic failure rate of just 3.5%, significantly below the 20% accepted virologic failure rate used to define adherence threshold requirements in older studies. 20 Despite the notable improved potency of newer first-line ARVs compared with ARVs of the 2000s, the goal for ART adherence remains 100% given the complexity of some ART regimens, the risk of developing resistance to ARVs, the effect of inflammatory processes, and increased mortality with suboptimal adherence. 20,21 Adherence to ART regimens for adolescents and young adults living with HIV (YLH) is often less than optimal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An 80-90% medication progression ratio to each of the three regimens was found to be associated with a virologic failure rate of just 3.5%, significantly below the 20% accepted virologic failure rate used to define adherence threshold requirements in older studies. 20 Despite the notable improved potency of newer first-line ARVs compared with ARVs of the 2000s, the goal for ART adherence remains 100% given the complexity of some ART regimens, the risk of developing resistance to ARVs, the effect of inflammatory processes, and increased mortality with suboptimal adherence. 20,21 Adherence to ART regimens for adolescents and young adults living with HIV (YLH) is often less than optimal.…”
mentioning
confidence: 99%
“…20 Despite the notable improved potency of newer first-line ARVs compared with ARVs of the 2000s, the goal for ART adherence remains 100% given the complexity of some ART regimens, the risk of developing resistance to ARVs, the effect of inflammatory processes, and increased mortality with suboptimal adherence. 20,21 Adherence to ART regimens for adolescents and young adults living with HIV (YLH) is often less than optimal. A 2014 systematic review and meta-analysis of adherence to ART among YLH (ages of [12][13][14][15][16][17][18][19][20][21][22][23][24] across the globe identified that overall only 62.3% were adherent to their therapy regimens.…”
mentioning
confidence: 99%
“…In comparison, two out of three macaques having plasma drug concentrations similar to those of simulated patients had high viral loads and significant resistance within the first 42 weeks of therapy 5. For the treatment combination, predictions of virological failure (green bars) are displayed along a regression curve that is based on clinical data 9. Compared to the regression curve, more virtual patients having an adherence level between 20% and 60% experienced virological success.…”
Section: Resultsmentioning
confidence: 99%
“…This choice was driven by the availability of virological failure data5, 9, 10 and the required parameters for the model (lymph node drug penetration,8 see below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation